The role of lifestyle physical activity in preventing multiple sclerosis - Opara, Józef (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Multiple sclerosis (MS) is a devastating neurodegenerative disorder that affects more than three million people worldwide.Among the environmental, lifestyle, dietary, comorbid, and pharmacological factors investigated as possible modifiable protective or risk factors for MS, physical activity (PA) seems to play a valuable role in its prevention. Currently, there is nocomprehensive review article on the preventive effects of PA in MS. This narrative review aimed to evaluate the most recentand extensive pooled analysis and evidence and to explore the influence of lifestyle PA on primary and secondary preventionin MS. Literature articles were searched through several databases, including PubMed, Cochrane Library, Embase, andWeb of Science, from 1985 to March 2024. The review focused on lifestyle PA, defined as the daily accumulation of at least30 min of self-selected activities. This includes all leisure, occupational, or household activities that are at least moderate tovigorous in intensity and may be planned or unplanned activities that are part of everyday life. The most valuable and representative reports on primary and secondary prevention in MS have been selected. Lifestyle PA, practised at moderate andhigh intensity, plays a protective role in reducing the risk of developing MS and delaying the onset of disability in personswith MS. Future studies are required to identify specific types of PA that are particularly recommended for patients with MS.
Keywords: prevention; physical activity; multiple sclerosis (MS); disability